Global Protoplanetary Disk Simulations: Dead Zone Formation and FUor Outbursts. Issue Volume 14:Issue S345(2019) (August 2018) - Kadam, Kundan; Vorobyov, E.; Regály, Zs.; Kóspál, Á.; Ábráham, P.
Abstract: We conducted global hydrodynamic simulations of protoplanetary disk evolution with an adaptive Shakura-Sunyaev α prescription to represent the layered disk structure, and starting with the collapse phase of the molecular cloud. With the canonical values of model parameters, self-consistent dead zones formed at the scale of a few au. The instabilities associated with the dead zone and corresponding outbursts, similar to FUor eruptions, were also observed in the simulations.